Pre-dive Whole-Body Vibration Better Reduces Decompression-Induced Vascular Gas Emboli than Oxygenation or a Combination of Both - Balestra, Costantino; Theunissen, Sigrid; Papadopoulou, Virginie; Le Mener, Cedric; Germonpré, Peter; Guerrero, François; Lafère, Pierre (Frontiers in Physiology, 2016)
Purpose: Since non-provocative dive profiles are no guarantor of protection against decompression sickness, novel means including pre-dive “preconditioning” interventions, are proposed for its prevention. This study investigated and compared the effect of pre-dive oxygenation, pre-dive whole body vibration or a combination of both on post-dive bubble formation. Methods: 6 healthy volunteers performed 6 no-decompression dives each, to a depth of 33 mfw for 20 minutes (3 control dives without preconditioning and 1 of each preconditioning protocol) with a minimum interval of 1 week between each dive. Post-dive bubbles were counted in the precordium by two-dimensional echocardiography, 30 and 90 minutes after the dive, with and without knee flexing. Each diver served as his own control. Results: Vascular gas emboli (VGE) were systematically observed before and after knee flexing at each post-dive measurement. Compared to the control dives, we observed a decrease in VGE count of 23.8±7.4% after oxygen breathing (p<0.05), 84.1±5.6% after vibration (p<0.001), and 55.1±9.6% after vibration combined with oxygen (p<0.001). The difference between all preconditioning methods was statistically significant. Conclusions: The precise mechanism that induces the decrease in post-dive VGE and thus makes the diver more resistant to decompression stress is still not known. However, it seems that a pre-dive mechanical reduction of existing gas nuclei might best explain the beneficial effects of this strategy. The apparent non-synergic effect of oxygen and vibration has probably to be understood because of different mechanisms involved.